Professional Orientation for Students of Health Courses Study conducted at a Public University in Northern Brazil - Albuquerque, Luiz Carlos Cavalcanti de; DA LUZ NETO, LEONARDO SEVERO; Almeida, Helio Franklin Rodrigues de; Viana, Teresinha Cícera Teodora; Gomes, Ariel Alves; Freitas, Paulo Vítor Alves de; Vieira, Thainá Loras (International Journal for Innovation Education and Research, 2019)
This article deals with the results of a research that integrated part of the discipline of Professional Guidance, given in the eighth period of the Psychology course of the Federal University of Rondônia, having as subjects, students of the health courses of a university of western Amazonia. Its objectives include: knowing the type of professional orientation offered in this context, the type of orientation that the students point out as necessary, proposing actions in response to the students' demands. In line with the problem investigated, and in light of the study's main objectives, a descriptive research line was adopted with data collection through interview. Besides being one of the most used in educational research, it presents itself as the most adequate for the proposed objectives. This research has provided a greater theoretical and practical knowledge of the theme orientation and has led to innovative reflections on inciting questions, also opens up new possibilities for research and interest so that further study of this subject can be carried out, not only about the objectives proposed in this work, but also the inferences extracted with a more general character, that can formulate some suggestions of improvement of the analyzed situation.